Service Level Agreements and Key Performance Indicators in Accountancy Outsourcing - Świetla, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
As the world economy has grown, the global service sector has evolved, and outsourced accounting services have seen the most robust growth of all. As a result, cooperation between the entity purchasing the service of separated processes and the service provider is becoming more and more common. Outsourcing external services allows organisations to reduce costs and ensure access to the latest technological solutions as well as to save time, which the contractor can use for its primary activity. To achieve success within the framework of bilateral cooperation, it is necessary to refine the design of both the contract concluded between the parties along with its specification in the form of a service level agreement (SLA) as well as the correct selection of key indicators (KPI) to assess the effectiveness of the benefits purchased. Thus, the article presents the principles of construction on contracts regarding the use of relevant services and the principles underlying the basics of indicators to assess their quality. The content of the article has been prepared on the basis of the subject literature, legal regulations and online source materials, including a review of reports presenting the use of SLA and KPI for the purposes of assessing the level of service provision.